2020
DOI: 10.1111/raq.12503
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted applications of probiotic Bacillus species in aquaculture with special reference to Bacillus subtilis

Abstract: Microorganisms play an important role in water quality maintenance, waste management, productivity enhancement, nutrient cycling, functional feed development, protection against infectious diseases, delivery of antigens and several other health benefits in aquaculture. The most significant use of microbes in aquaculture to minimize the antibiotics and drugs is through probiotics. The scope of probiotics in modern aquaculture has been enormous due to the detrimental consequences of routinely used antibiotics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(46 citation statements)
references
References 356 publications
(612 reference statements)
1
42
0
3
Order By: Relevance
“…Bacillus subtilis , one of the most well-researched probiotics, has been widely used as a direct-fed microbial (DFM) feed supplement [ 16 , 17 ], thus improving feed digestion and utilization via regulating intestinal flora [ 18 ]. Furthermore, it enhances immunity [ 19 ] and the growth performance of the animal via secretion of various digestive enzymes [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus subtilis , one of the most well-researched probiotics, has been widely used as a direct-fed microbial (DFM) feed supplement [ 16 , 17 ], thus improving feed digestion and utilization via regulating intestinal flora [ 18 ]. Furthermore, it enhances immunity [ 19 ] and the growth performance of the animal via secretion of various digestive enzymes [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria have been identified as the major colonizer within the GI tract of fish. Moreover, copious reports have indicated that genus Bacillus dominates the bacterial community in carps and other freshwater teleosts (for review, see Ghosh et al, 2021;Nayak, 2021;Ray et al, 2012;Soltani et al, 2019). Culture independent studies comprising of high-throughput sequencing also recognized the phylum Firmicutes (to which genus Bacillus belongs) as a dominant group within the carp GI tract (Foysal et al, 2019;Mukherjee et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, several studies have demonstrated probiotic potential of the Bacillus spp. in aquaculture, and their application has been suggested to improve growth, immunity and disease resistance in fish (for review, see Soltani et al, 2019;Nayak, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Bakterija daro teigiamą poveikį vandens augmenijai ir gyvūnijai, ko pasekoje gerėja ir jūros gėrybių vartotojų sveikata. (Nayak, 2021). 2021 metais publikuotame Nair ir kitų autorių straipsnyje buvo teigiama, kad Bacillus subtilis panaudojimas akvakultūroje prailgino vandens gyvūnų gyvenimo trukmę.…”
Section: Vandens Kokybėunclassified